Ansatz de Bethe para cadeias quânticas de spin-1 com condições de contorno - Fireman, Elton Casado (2002)
The procedure for obtaining integrable open spin chain Hamiltonians via reflection matrices explicitly carried out for some three-state vertex models. We have considered the 19-vertex models of Zamolodchikov-Fateev and Izergin-Korepin and the Z2 graded 19-vertex models with sl(2/1) and osp(1/2) invariances. In each case the eigenspectrum is determined by application of the coordinate Bethe ansatz.